Fabrication of superhydrophobic PDTS-ZnO-PVDF membrane and its anti-wetting analysis in direct contact membrane distillation (DCMD) applications - Li, Jun; Ren, Long-Fei; Zhou, Hong Susan; Yang, Jingren; Shao, Jiahui; He, Yiliang (Journal of membrane science, 2021)
Membrane distillation (MD) is an emerging water treatment technology suitable for hypersaline wastewater. However, membrane wetting is a primary obstacle to restrict its widespread industrial use. In this study, a superhydrophobic nanofibrous membrane (labeled as FZP) with high water contact angle of 162.3° and sliding angle of 9.8° was fabricated through fluorinating of zinc oxide (ZnO) blended electrospun polyvinylidene fluoride (PVDF) membrane. In comparison with neat and ZnO blended PVDF (ZP) nanofibrous membranes, FZP membrane has much better anti-wetting property due to its superhydrophobicity and higher liquid entry pressure (LEP) value when desalinating both pure NaCl solution and NaCl solutions with low-surface-tension sodium dodecyl sulfate (SDS) and sparingly soluble salt CaSO4. LEP values of membranes for SDS and CaSO4 contained feed solutions were calculated to be smaller than that for pure NaCl solution, accelerating the occurrence of membrane wetting. Temperature gradient across the membrane and Gibbs free energies of CaSO4 heterogeneous nucleation were further calculated to elucidate the wetting mechanism. Our results provide valuable insights for better developing superhydrophobic membrane and understanding its anti-wetting property in MD process. [Display omitted] •Superhydrophobic FZP membrane was facilely obtained by ZnO blending and fluorination.•The highest LEP and lowest transmembrane ΔT led to best anti-wetting performance.•The highest ΔGheterogeneous of CaSO4 is least prone to membrane hydrophilization.